The incidence and risk factors of intraoperative bacterial contamination in primary total knee arthroplasty - Xing, Lijun; Liu, Fengyue; Li, Enrun; Kang, Yuling; Tan, Kunyuan; Li, Juhong (Frontiers in Surgery, 2024)
BackgroundInfection is a devasting complication after arthroplasty. Identifying potential sources contributing to intraoperative bacterial transmission can help to reduce surgical-site infections.ObjectiveThe aim of this study was to identify the incidence and risk factors of intraoperative bacterial contamination (IBC) in primary total knee arthroplasty (TKA) procedures.MethodsActive surveillance cultures were used to detect IBC from 125 consecutive unilateral primary TKAs. The cultures were taken from different sites (surgical instruments, gloves of surgeons and surgical incisions) at different time points (before surgery, 30 min and at the end of the surgery) during arthroplasty procedures. Patient characteristics, including age, height, body weight, body mass index, comorbidity of diabetes mellitus, operative duration, intraoperative blood loss, types of prophylactic antibiotics were recorded. The white blood cell level before, the 3rd and 7th day after surgery were measured and recorded. In addition, patients were also followed for fever and surgical-site infections within 14 days after surgery.ResultsIn total, 1,000 cultures were taken. 91 (9.1%) of them showed an IBC. None of bacterial cultures of gloves and instruments before surgery were positive. At 30 min from the beginning of the procedure, 29 cultures (7.7%) from 16 patients (12.8%) showed a contamination. At the end of the surgery, 62 cultures (16.5%) from 32 patients (25.6%) showed a contamination. There were 15 cases (12.0%) of fever within 14 days after surgery, of which 11 cases with IBC, and 4 cases without IBC. No postoperative surgical-site infection occurred in all consecutive unilateral primary TKAs. The binomial logistic regression analyses confirmed that operative duration was the risk factor of IBC [OR 1.137 (95% CI 1.023 to 1.322), p = 0.014]. Moreover, compared to control group, the patients with IBC had a greater change of white blood cell level in the 3rd day after surgery (p = 0.022), and a higher risk of fever within 14 days after surgery (p < 0.001).ConclusionThe bacterial contamination rate during primary TKA is relatively high, despite the practice of standard preventive measures. Intraoperative bacterial contamination increases with long operating time, which may be one of the factors contributing to fever and leukocytosis after surgery.